Modelamento, simula??o e an?lise de desempenho de um comutador ATM CIOQ - Aguiar Filho, Sebasti?o Rodrigues de (2005)
Abstratc: blocking probability and the average queue length in the input and in the second case, with queues with priorities. the average queue length was measured both at the entrance as the output for each priority class. To model the switches and perform the simulations we used the simulation software ARENA 5.0 discrete event (Rockell Software). One of the objectives of this study is to compare / verify the analytical results and simulated results obtained using the Matlab software at a previous job. with low blocking probabilities and also low average queue lengths for the simulated parameters.